As linguagens poéticas das crianças na Educação Infantil: seus meios de ser, imaginar e expressar sentidos - Pereira Junior, Leandro da Silva (2024)
This research focuses on the poetic languages of children in Early Childhood Education (ECE), specifically a preschool class of Infantil V in Fortaleza-CE, aiming to investigate how they employ their diverse expressions that touch on aesthetics. It proposes to identify the poetic languages experienced and constructed by the children, in contexts coordinated or not by the teacher/researcher, and to grasp the meanings they attribute to their lived experiences through their narratives and poetic manifestations. Theoretically, it discusses the importance of cultivating an understanding of the child in becoming (Kohan, 2005), who lives the world by appropriating languages to feel and exist in the spaces they inhabit (Vygotsky, 2007), with the ECE space as an important facilitator of aesthetic experiences (Hoyuelos, 2020), where children use means of being, imagining, and expressing senses through poetic languages (Vecchi, 2017) to produce their sensitive understandings of what surrounds them, thus developing their subjectivity and identity. It is characterized as a qualitative research with (auto)biographical approach (Delory-Momberger, 2012a; Pineau, 2014), focusing on poetic languages from the children's perspective (Passeggi, 2018), bringing their ways of being, imagining, and expressing into dialogue, based on their choices, perceptions, and interactions, lived and manifested, understanding that, in this process, they constitute themselves, autobiographize themselves (Goldberg, 2016). A phenomenological stance (Frota, 2010) is used to access how children experience the world poetically. Data construction was through participant observation (Minayo, 2016), itinerancy diary (Barbier, 2007), photographic, videographic records, and voice recording, which, along with pedagogical documentation (Forman; Fyfe, 2016), gathered what was observed and reflected upon in the field research. The experiences and materials produced by the children were shared and discussed in conversation circles, creating a narrative and dialogical space called Dialogical Atelier with Children (DAC), aiming to access the meanings they attribute to poetic languages. As a result, it was possible to access various poetic languages that the participating children used, such as sculpture, drawing, painting, dramatization, projection, make-believe, among others, expressed in different spaces and times of preschool, to establish their meanings, their significances, and their understandings of the experienced. Contact with their poetic expressions testifies to how their theories, knowledge, and hypotheses are woven, largely through metaphor, analogy, aesthetic dimension, and the stories and memories that are part of their lives and life stories. In this way, it was also noted that they relaunch with creativity, imagination, and experiential repertoire (familial, educational, cultural, and social) the poetic crossings that the preschool context offers, favors, and provides opportunities for. Finally, we understand that poetic languages enable children strategies for insertion, connection, and construction of themselves in a more sensitive way in the world, being essential to learn to listen-see with all our senses what they have to tell and teach us about them, with them, and from them.